2002
DOI: 10.1300/j087v37n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Does Parental Involvement Eliminate the Effects of Parental Divorce on the Academic Achievement of Adolescents?

Abstract: Publication details, including instructions for authors and subscription information:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
(36 reference statements)
2
11
0
1
Order By: Relevance
“…Of the three racial groups included in this study, African American children are most likely to come from single-parent families, Latino children are the second most likely to come from this family structure, and Asian Americans are least likely to come from this family structure (Jeynes 1998(Jeynes , 2002. Research supports the notion that family structure is the most important facet of parental involvement (Jeynes, 2001).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Of the three racial groups included in this study, African American children are most likely to come from single-parent families, Latino children are the second most likely to come from this family structure, and Asian Americans are least likely to come from this family structure (Jeynes 1998(Jeynes , 2002. Research supports the notion that family structure is the most important facet of parental involvement (Jeynes, 2001).…”
Section: Discussionsupporting
confidence: 58%
“…The presence of more parents in the workforce, the fast pace of modern society as a whole, and the declining role of the family have all been reasons that some social scientists have pointed to to explain an apparent decline in parental involvement in education (Coleman & Hoffer, 1987;Jeynes, in press). Although many educators have highlighted the importance of parental involvement if children are to do well in school, the research that has been done on this issue has frequently been unable to give guidance regarding the extent to which parental involvement helps student achievement and just what kind of parental involvement is most important (Jeynes, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the negative impact of divorce on child academic outcomes is a consistent finding in the literature (Barber, 1998;Bertram, 2006;Jeynes, 2002;Kelly & Emery, 2003;McLanahan, 1999). Children from divorced families have lower math, reading and standardized test scores (Sun & Li, 2002).…”
Section: Cross-culturalsupporting
confidence: 66%
“…Research has shown that students whose either parents or both parents are absent in families have poor grades (Balli et al, 1998;Teachman et al, 1995). Apart from the financial hardship in the broken family (Sun and Li, 2001), inadequate parental socialization is a reason for the academic deficit (Jeynes, 2002). The inadequate socialization largely consists of the absence of either paternal or maternal socialization, which is essential for proper gender role socialization (Hetherington et al, 1983).…”
Section: Potential Contributions Of Socialization Factorsmentioning
confidence: 99%